Analisis Debit Air Limpasan Permukaan (Run Off) Akibat Perubahan Tata Guna Lahan Pada DAS Kuranji Dan DAS Batang Arau Kota Padang - Madhatillah Madhatillah; Rusli HAR (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. Changes in land use from catchment areas to densely populated areas are the main factors causing high runoff discharge values. This is because vegetation that serves to absorb water into aquifers is not optimal. So that rainwater that falls to the surface of the land continues to wave into lakes, rivers, and seas without entering and seeping into aquifers. As a result, the value of the runoff until it reaches the sea becomes large. For this reason, a study needs to be carried out to determine the volume of runoff discharge due to landuse changes such as what has been done in the Kuranji and Batang Arau Watersheds of Padang City. This research was conducted in 2 watersheds in the Padang City watershed and made into several subwatersheds to get more specific results. The data obtained are secondary in the form of daily rainfall data in 8 active rainfall measuring stations in the city of Padang for the past 10 years (2009-2018), planned discharge data in 2000, map data in the form of shapefiles. Based on data processing using the Rational large discharge method for the 25 year return period in the Kuranji watershed with a watershed area of 220,687 km2 and a runoff coefficient of 0,64 amounted to 1315,70 m3/second. This discharge value has increased by 445 m3/second compared to the value of the existing discharge plan in 2000 of 870 m3/second. In Batang Arau watershed, the discharge value with an area of 177,1386 km2 and a large runoff coefficient of 0,68 is 1192,57 m3/second. This debit value increased by 492,57 m3/second from the planned discharge in 2000 of 700 m3/second.Keywords: RunOff,Landuse, Kuranji’s Watersheds, Batang Arau’s Watersheds, and Rational